Further evidence on the bank lending process and the capital-market response to bank loan agreements - Lummer, Scott L.; McConnell, John J. (Journal of Financial Economics, 1989)
This paper investigates the hypothesis that bank loans convey information to the capital market regarding the value of the borrowing firm. Unlike previous researchers, we distinguished between new bank loans and loan renewals. For new loans, the excess stock return for borrowers around the loan announcement is not significantly different from zero. For favorable loan revisions, the excess return is significantly positive: for unfavorable revisions, it is significantly negative. We interpret these results to imply that banks play an important role as transmitters of information in capital markets, but new bank loans per se do not communicate information.